3-D shell analysis of structure in portal section of mountain tunnel under seismic SH wave action. (February 2015) - Tao, Lianjin; Hou, Sen; Zhao, Xu; Qiu, Wenge; Li, Tianbin; Liu, Chunxiao; Wang, Ke
Highlights: Analytical solutions of earthquake-induced strains for tunnel portal section are proposed. The approach takes into account for the effect of the free surface slope on wave reflection. Hoop strain mainly concentrates in both sides of springing and spandrel of lining. Shear strain mainly concentrates in the crown and invert of lining. Abstract: Tunnel portals are often located in rather weak rock. Also the ground surface of tunnel portal section is often inclined to form slopes. These characteristics in engineering geology make this section easy to be damaged during earthquakes both in slope and in structures. A model with single free surface slope is built to analyze the dynamic response of portal section of a mountain tunnel. First, the theory of elastic wave propagation is used to deduce the solution of free field ground motion on the axis of tunnel under incident SH wave without considering the existence of the tunnel. Then, the ground motions are putting on tunnel structure, where the 3-D elastic shell theory is employed in order to provide strains of the structure. The analytical solutions of the model are verified by the results of shaking table test. In this way, the analytical solutions do not only consider the amplitude-time–frequency effects, but also derives analytical expressions of axial, hoop and shear strain distribution on tunnel cross-sections. These results could be references for seismic design of tunnel portal section in mountain tunnels and have positive effects on reasonable understandings of the seismic response characteristics in this section.